2013
DOI: 10.1126/scitranslmed.3006373
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism for Age-Related Memory Loss: The Histone-Binding Protein RbAp48

Abstract: To distinguish age-related memory loss more explicitly from Alzheimer’s disease (AD), we have explored its molecular underpinning in the dentate gyrus (DG), a subregion of the hippocampal formation thought to be targeted by aging. We carried out a gene expression study in human postmortem tissue harvested from both DG and entorhinal cortex (EC), a neighboring subregion unaffected by aging and known to be the site of onset of AD. Using expression in the EC for normalization, we identified 17 genes that manifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 50 publications
8
100
1
Order By: Relevance
“…The NuRD complex is the only RBBP4-containing complex known to interact with the PHF6 protein, but it is possible that PHF6 might associate with other RBBP4-containing complexes, such as the CAF-1 and PRC2 complexes, in a parallel manner. RBBP4/RbAp48 decline in the dentate gyrus is responsible for age-related memory loss (37), and the PHF6 gene is associated with human Börjeson-Forssman-Lehmann syndrome, an X-linked mental retardation disorder, and is also expressed in the dentate gyrus in the adult brain (17). However, it is unclear whether there is a relationship between RBBP4-PHF6 interaction and human mentality and memory.…”
Section: Phf6 Mutations Might Affect the Developmental Pathways Regulmentioning
confidence: 99%
“…The NuRD complex is the only RBBP4-containing complex known to interact with the PHF6 protein, but it is possible that PHF6 might associate with other RBBP4-containing complexes, such as the CAF-1 and PRC2 complexes, in a parallel manner. RBBP4/RbAp48 decline in the dentate gyrus is responsible for age-related memory loss (37), and the PHF6 gene is associated with human Börjeson-Forssman-Lehmann syndrome, an X-linked mental retardation disorder, and is also expressed in the dentate gyrus in the adult brain (17). However, it is unclear whether there is a relationship between RBBP4-PHF6 interaction and human mentality and memory.…”
Section: Phf6 Mutations Might Affect the Developmental Pathways Regulmentioning
confidence: 99%
“…Bioelectrical activity of the neurons in mollusks and warmblooded animals is mainly provided by the ac tivity of sodium, calcium and potassium ion channels, which are built and operate according to the same general principles [3][4][5][6][7][8]. It enable us to use the neu rons of mollusks as eligible models [9][10][11][12][13][14][15][16][17][18], in paral lel with the neurons of warmblooded animals, for experimental research on the performance of the ion channels and the mechanisms of influences on them made by various physical factors, chemical substanc es and pharmaceutical drugs either of already known nature or being designed.…”
Section: Methodsmentioning
confidence: 99%
“…Extensive investigations have focused on the hippocampus to form a conceptual framework of the architecture of diverse memory systems. It is well understood that RbAp48 participates in the age-related DG dysfunction and the expression level decreases in ageing hippocampus of human and mice [12,18]. The deficiency of RbAp48 in the DG has been suspected as the underlying cause of age-related memory deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a longer duration of refractory TLE would exhibit more severe cognitive impairments. Understanding of the neurobiology of disordered cognition especially the memory loss in epilepsy was accelerated by the development of organized epilepsy surgery Furthermore, it had been found that up-regulation of RbAp48 in the DG of aged wild-type mice ameliorated their age-related memory loss, and restored their memory to youthful vigor [12]. So it is a logical next step to test these RbAp48 expression enhancers for therapeutic use against the memory deterioration in TLE animal models, and ultimately in TLE patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation